Multiple drug resistance caused by germline mutation of exon 27 of BRCA2 gene in triple-negative breast cancer: a case report and literature review - Li, Yuting; Xu, Guojie; Zhang, Liling; Zhao, Kewei; Zhao, Yanxia; Han, Dan (Frontiers in Oncology, 2025)
BRCA genes, including BRCA1 and BRCA2, are tumor suppressor genes that play a crucial role in the HRR pathway for double-strand DNA breaks. Mutations in these genes lead to the loss of function of their respective proteins, resulting in HRD and the development of hereditary breast cancer. The BRCA2 gene is located on chromosome 13 at the 13q12.3 region and spans 84kb with 27 exons. Frame shift mutations are the most common pathogenic genetic alterations observed in BRCA2, particularly within exons 3, 7, 10, 11, 17, 18, 23 and notably exon 11. Breast cancer patients carrying BRCA1/2 mutations are typically responsive to platinum-based chemotherapy as well as radiation therapy and PARP inhibitors due to their impaired HRR capacity. In this case, a sporadic frameshift mutation was identified in exon 27 of the BRCA2 gene, which has not been previously reported. Studies indicate that mutations occurring within exon 27 disrupt the binding between BRCA2 and RAD51 C-terminal domain resulting in embryonic damage and significantly reduced lifespan based on mouse models of breast cancer. Notably, the patient’s mother and grandmother harbor pathogenic point mutations in BRCA2 on chromosome 13, specifically c.10255dup p. Ter3419LeufsTer19. The patient, a young TNBC, exhibited distinct genetic pathogenic features and changes in the BRCA mutation site. Despite undergoing treatment, the patient experienced rapid recurrence and demonstrated resistance to chemotherapy, PARP inhibitors, and immunotherapy, while remaining sensitive to radiotherapy. This case may serve as a valuable reference for diagnosing and treating breast cancer associated with BRCA2 exon 27 mutations.